Relational Contracts and Organizational Capabilities - Gibbons, Robert; Henderson, Rebecca (Organization Science, 2012)
A large literature identifies unique organizational capabilities as a potent source of competitive advantage, yet our knowledge of why capabilities fail to diffuse more rapidly—particularly in situations in which competitors apparently have strong incentives to adopt them and a well-developed understanding of how they work—remains incomplete. In this paper we suggest that competitively significant capabilities often rest on managerial practices that in turn rely on relational contracts (i.e., informal agreements sustained by the shadow of the future). We argue that one of the reasons these practices may be difficult to copy is that effective relational contracts must solve the twin problems of credibility and clarity and that although credibility might, in principle, be instantly acquired, clarity may take time to develop and may interact with credibility in complex ways so that relational contracts may often be difficult to build.